Implementation of Information Technology in Supporting Kurikulum Merdeka - Wulaningsih, Rusti; Radiana, Usman (Universitas Negeri Jakarta, 2024)
Background The information technologies used include the Platform Merdeka Mengajar (PMM), info GTK, Learning Management System (LMS) for Guru Penggerak, and various digital initiatives under the Sekolah Penggerak program. Purpose This study aims to analyze the implementation of information technology in supporting the execution of the Kurikulum Merdeka in schools across Indonesia. Design/method/approach The research employed a qualitative approach, with data collection techniques including interviews, observations, and document analysis. Data were obtained from relevant stakeholders, such as teachers, principals, and education staff from several schools that have adopted the Kurikulum Merdeka. Results The results showed that the use of information technology has enhanced the effectiveness of teaching, facilitated collaboration among teachers, and improved access to more diverse and structured learning resources. However, the main challenges include limited infrastructure in some schools and the need to improve digital literacy among teachers and education staff. Contribution/value In conclusion, information technology plays a significant role in supporting the implementation of the Kurikulum Merdeka, but its success requires adequate infrastructure and enhanced digital skills.